Pitting Corrosion Resistance and Repassivation Behavior of C-Bearing Duplex Stainless Steel - Hanme Yoon; Heon-Young Ha; Tae-Ho Lee; Sung-Dae Kim; Jae Hoon Jang; Joonoh Moon; Namhyun Kang (Metals, 2019)
The effects of C-substitution for part of the N content, on the pitting corrosion resistance and repassivation tendencies of duplex stainless steels (DSSs) were investigated. For this investigation, normal UNS S32205 containing N only (DSS-N) and the C-substituted DSS (DSS-NC) were fabricated. Microstructural analyses confirmed that the two DSSs had dual-phase microstructures without precipitates, and they possessed similar initial microstructure, including their grain sizes and phase fractions. Polarization and immersion tests performed in concentrated chloride solutions revealed that the DSS-NC was more resistant against stable pitting corrosion and possessed a higher repassivation tendency than the DSS-N. Furthermore, the corrosion pits initiated and propagated to a less corrosion resistant α phase. Polarization tests and corrosion depth measurements conducted in an HCl solution indicated that the DSS-NC exhibited lower galvanic corrosion rate between the α and γ phases than the DSS-N. Therefore, the growth rate of pit embryo was lowered in the DSS-NC, which shifted the potentials for the stable pit initiation and the pit extinction to the higher values.